Video company profile Sebagai Media Diseminasi Informasi Potensi Desa Jemah - Saepudin, Encang; Sugito, Toto; Komariah, Kokom (Innovative: Journal Of Social Science Research, 2024)
Jemah Village has extraordinary potential, both natural tourist destinations and artificial tourist destinations, social culture, agriculture and animal husbandry. The potential of Jemah Village, especially the potential for natural and artificial tourism, needs to be known by people outside Jemah Village. Knowing this potential will increase tourist visits. The aim of the research is to create a company profile video as a medium for disseminating information on the potential of Jemah Village. The method used is action research using the Kurt Lewin model which consists of four components, namely planning, action, observation and reflection. The resource persons consisted of the Jemah village head, community leaders and youth leaders. Data collection techniques through interviews, observation and literature study. The research results show that making a company profile video goes through the stages of planning, action, observation and reflection. The conclusion that can be drawn is that the Jemah Village company profile video can be a medium for disseminating information on the village's potential and a promotional medium for tourist destinations